317Neighbourhood built and social environmental attributes associated with frailty among mid-to-older aged Australian adults. (2nd September 2021) - Abe, Takumi; Sugiyama, Takemi; Carver, Alison; Turrell, Gavin
Abstract: Background: Little is known about to what extent neighbourhood built and social environmental factors are associated with frailty among community-dwelling mid-to-older aged adults. Methods: Participants of our cross-sectional study were adults aged 50-74 years residing in Brisbane, Australia. Frailty was assessed by a frailty index (FI), consisting of 32 items. Five built environmental attributes (population density, density of 4-way intersections, area of retail land, area of park land, and area of land for recreational facilities) and three social environmental attributes (safety, cohesion, and socio-economic status [SES]) were included. We performed multilevel logistic regression analysis to examine the associations between those attributes and frailty. Results: Of 4, 176 eligible participants (56.8% women), we found that 437 (10.5%) were frail (FI ≥ 0.35). After adjusting for potential confounders, one standard deviation (SD) increment in intersection density and retail land area was associated 26% (95%CI: 1.12, 1.41) and 18% (95%CI: 1.07, 1.30) higher odds of being frail, respectively. One SD increment in safety and area-level SES was associated with 24% (95%CI: 0.69, 0.84) and 30% (95%CI: 0.62, 0.79) lower odds of being frail. Conclusions: This study found that mid-to-older aged adults with frailty are more likely to live in areas with higher intersection density, greater area of retail land, poorer safety, and higher levels of deprivation. Key messages: There is spatial heterogeneity in the distribution of frailty. Future research should investigate behavioural mechanism for the distribution.